A relação entre psoríase e psicoses - Pedro Manuel Bento Gonçalves (2020)
Background: Psoriasis is a chronic and immune disorder characterized for the appearance of red elevated skin lesions. For this reason, this disease has a great impact in patients' mental health. It is expected that the unfold of this skin disorder is connected to psychotic events or other psychotic pathologies. However, there is a lack of research concerning this relation. Methods: A review about articles published in Portuguese and English on psoriasis and psychotic disorders was performed. Results: When compared to healthy individuals, psychotic patients present a higher risk to get psoriasis, or to suffer a worse development in an existing psoriatic disorder. The same can be said about an individual with psoriatic lesions, as they are linked to a worse scenario in terms of psychotic disorders. These diseases seem to share genetic, immune and inflammatory characteristics which could explain their connection. The adverse effects derived from using Olanzapine, Quetiapine, Aripiprazole and Lithium carbonate, used in the treatment of psychosis, as well as the use of Ciclosporin and Etanercept, antipsoriatic drugs, can be another explanation for this link. Conclusion/Discussion: At this point in time, there is still a small number of papers on this subject. Thus, further research is needed to understand the connection between psoriasis and psychotic disorders. The understanding of the correlation between these pathologies would be beneficial for a better prognosis and fewer comorbidities, and ultimately for more effective treatment.